2016
DOI: 10.1002/dneu.22372
|View full text |Cite
|
Sign up to set email alerts
|

ZDHHC16 modulates FGF/ERK dependent proliferation of neural stem/progenitor cells in the zebrafish telencephalon

Abstract: In vertebrates, neural stem/progenitor cells (NSPCs) maintenance is critical for nervous system development and homeostasis. However, the molecular mechanisms underlying the maintenance of NSPCs have not been fully elucidated. Here, we demonstrated that zebrafish ZDHHC16, a DHHC encoding protein, which was related to protein palmitoylation after translation, was expressed in the developing forebrain, and especially in the telencephalon. Loss- and gain-of-function studies showed that ZDHHC16 played a crucial ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Its name Ablphilin stems from its ability to interact with the non-receptor tyrosine kinase c-Abl at the ER surface ( Li et al, 2002 ). ZDHHC16/Aph2 is essential for embryonic and postnatal survival, eye and heart development in mice ( Zhou et al, 2015 ), for the proliferation of neural stem cells, where it is involved in the activation of the FGF/erk pathways ( Shi et al, 2016 ) and was reported to play a role in DNA damage response ( Cao et al, 2016 ). Our findings raise the possibility that some of these effects may involve ZDHHC6.…”
Section: Discussionmentioning
confidence: 99%
“…Its name Ablphilin stems from its ability to interact with the non-receptor tyrosine kinase c-Abl at the ER surface ( Li et al, 2002 ). ZDHHC16/Aph2 is essential for embryonic and postnatal survival, eye and heart development in mice ( Zhou et al, 2015 ), for the proliferation of neural stem cells, where it is involved in the activation of the FGF/erk pathways ( Shi et al, 2016 ) and was reported to play a role in DNA damage response ( Cao et al, 2016 ). Our findings raise the possibility that some of these effects may involve ZDHHC6.…”
Section: Discussionmentioning
confidence: 99%
“…ZDHHC16 was a DHHC encoding protein, which was tightly correlated with protein palmitoylation in previous researches [39]. Wei Shi et al reported that ZDHHC16 acted as a vital regulator in the process of NSPCs proliferation [40]. Li Jian et al uncovered pivotal players for ZDHHC16 in the regulation of DNA damage responses and Atm activation [41].…”
Section: Discussionmentioning
confidence: 96%
“…Embryos were immersed in 10 mM BrdU solution at 28.5 • C for 4 h after peeled off the chorion manually with #5 watchmaker's forceps, and then embryos were fixed with 4% paraformaldehyde overnight at 4 • C. The next day, embryos were incubated with anti-BrdU antibody overnight and washed with PBST. After incubation with HRP secondary antibody for 1 h, DAB staining was performed to observe BrdU-positive cells (Shi et al, 2016).…”
Section: Bromodeoxyuridine Assaymentioning
confidence: 99%
“…Embryos were incubated in 2 µg/ml acridine orange solution at 28.5 • C for 30 min in the dark after peeled off the chorion. The embryos were analyzed by fluorescence microscope after washing the embryos with PBS (Shi et al, 2016).…”
Section: Acridine Orange Stainingmentioning
confidence: 99%